Decomposition of canola stubble by solid-state fermentation with Cyathus olla - Shinners-Carnelley, T.C.; Tewari, J.P. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2000)
Cyathus olla is being studied for its potential as an inoculant to accelerate decomposition of canola stubble, and hence to reduce the incidence of stubble-borne diseases of this crop. Stubble infested by C. olla appears soft and macerated, but the extent of decomposition incited by this fungus is not known. Composition of stubble fiber of five canola cultivars was determined with the Goering Van Soest method of fiber determination. Sterile canola (cv. Cyclone) substrate was inoculated with C. olla and incubated at 25 C for 45 days, followed by fiber analyses to detect changes in the fiber content. All cultivars were variable with respect to cell wall composition. Canola substrate inoculated with C. olla f. brodiensis had 60.6% of the original lignin remaining after incubation, compared to 65.9% for the substrate incubated with C. olla f. olla and 71.8% with C. olla f. anglicus. Hemicellulose content was reduced as only 75.3, 78.6, and 81.6% of the original hemicellulose content remained after incubation with C. olla f. brodiensis, C. olla f. olla, and C. olla f. anglicus, respectively. Cellulose was also degraded, and the neutral detergent soluble fraction increased. Cyathus olla was capable of degrading lignin in vitro, but field testing must follow to assess its decomposing activity under natural conditions.